Perception of Environmental Sanitation and Communication Practice in Port Harcourt Rivers State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study examined perception of environmental sanitation and communication practice in Port Harcourt, Rivers State, Nigeria. The study used multi-stage cluster sampling technique and respondents’ participatory interview. The study administered 400 questionnaires in the study area. The respondents’ participatory interview and questionnaires were administered in three clusters of the Diobu area, Government Residential Area (GRA) and other residential areas.  Findings of the study showed that the respondents understood that environmental sanitation is a practice of keeping the surrounding of man clean (34% agree and 61.5% strongly agree). The stakeholders’ response showed that their level of communicating environmental sanitation was majorly through radio, television and print media. The highest communication medium for environmental sanitation in the Port Harcourt was by radio (38.25% agree and 54.5% strongly agree). The television was adequately utilized to communicate environmental sanitation (38.75% agree and 50.75% strongly agree). The stakeholders were of the perception that government participated more in communicating environmental sanitation (34.5% agree and 35.5% strongly agreed). On the relationship of environmental sanitation occurrence and communication to stakeholders, the Chi-square test showed a table value of 37.12 and calculated value of 1.6962 indicating that the calculated value was lesser than the table value. This proved that environmental sanitation was not significantly communicated to the Port Harcourt city dwellers. This study, therefore, recommended that the government and policy makers should actively utilize the local and national media to communicate environmental sanitation in Port Harcourt, Rivers State of Nigeria.